2018
DOI: 10.1186/s12885-018-5008-z
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic acinar cell carcinoma—case report and literature review

Abstract: BackgroundPancreatic acinar cell carcinoma (ACC) is a rare tumor that constitutes 1% of all pancreatic neoplasms. Pancreatic ACC has unique characteristics in terms of biological behavior, imaging and prognosis.Case presentationThe present study reported two cases of pancreatic ACC confirmed by postoperative pathology and both cases exhibited several different imaging features and laboratory test results. Both cases had approximately 4 cm mass located in uncinate process of pancreas. Dilated intra- and extra-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[3] NETs usually show strong enhancement on postcontrast images and malignant IPMN is associated with dilatation of main pancreatic duct; both of these findings were absent in this case. Rare primary tumors associated with calcification include acinar cell carcinoma, [4] liposarcoma, and chondrosarcoma. [5] Some case reports have described psammomatous calcification within the primary adenocarcinoma of the pancreas.…”
Section: Review Of Literaturementioning
confidence: 99%
“…[3] NETs usually show strong enhancement on postcontrast images and malignant IPMN is associated with dilatation of main pancreatic duct; both of these findings were absent in this case. Rare primary tumors associated with calcification include acinar cell carcinoma, [4] liposarcoma, and chondrosarcoma. [5] Some case reports have described psammomatous calcification within the primary adenocarcinoma of the pancreas.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Acinar cell carcinoma (ACC) is a rare pancreatic epithelial malignancy derived mainly from pancreatic acinar cells and terminal branches of the pancreatic duct, accounting for approximately 1% of all pancreatic tumors ( 1 ). The hallmark pathological feature of ACC is its exocrine function and its potent capacity to invade and metastasize ( 2 ), which makes treatment of ACC more difficult than that of other pancreatic tumors and leads to an extremely pessimistic prognosis ( 3 ). The 5-year mortality rate of patients with ACC exceeds 50%, and its lethality ranks among the highest among all malignancies ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most malignant tumors originating from the exocrine pancreas are pancreatic ductal adenocarcinoma (PDAC), with pancreatic acinar cell carcinoma (PACC) accounting for less than 1% of primary pancreatic neoplasms [2][3][4]. Because of the rarity of PACC, it is difficult to know the exact characteristics of this disease and clinical course, as most studies reported to date only have limited numbers with data from single-center studies or multicenter studies [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%